Raiders and natives : cross-cultural relations in the age of buccaneers - Bialuschewski, Arne (Athens : The University of Georgia Press, 2022)
"Raiders and Natives illuminates the relationships among-and conflicts between-European buccaneers and various Indigenous peoples in Central America during the seventeenth century. Like many of the Natives they encountered on their frequent inland excursions, most of these buccaneers-chiefly those flying under English, French, and Dutch flags-also viewed the Spanish and their colonial regime as an enemy. While this sort of geopolitical situation led to martial alliances, it also resulted in a variety of cross-cultural exchange that altered sociopolitical organization, material culture, subsistence economies, and military strategies for all involved. Building on what one reviewer has called "immense archival research," Bialuschewski's study untangles the wide variety of forms this cross-cultural exchange took. Although a "mutually beneficial long-term alliance" emerged between buccaneers and Natives on the Miskito Coast in Nicaragua-and succeeded in holding off Spanish colonization until the nineteenth-century-elsewhere cultural exchange took the form of abduction, enslavement, and sexual assault. By placing these encounters at the center of Raiders and Natives, Bialuschewski changes our understanding of the early modern Atlantic World and the cross-cultural relations that shaped it"--
The Rise of the Buccaneers -- Mayas Besieged -- The Granada Raid -- Natives and Intruders in Central America -- Intercultural Alliances on the Mosquito Coast -- Shifting Alliances on Panamá's Darién Frontier -- The South Sea Incursions.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Indians of Central America -- History -- 17th century; Buccaneers; Pirates -- Central America -- History -- 17th century; Pirates -- Caribbean Area -- History -- 17th century; Indians, Treatment of -- Central America -- History -- 17th century; Central America -- History -- 17th century; Spain -- Colonies -- America -- History -- 17th century; Indians -- Central America -- History -- 17th century; Indiens d'Amérique -- Amérique centrale -- Histoire -- 17e siècle.; Attitudes envers les Peuples autochtones -- Amérique centrale -- Histoire -- 17e siècle.; Boucaniers; Pirates -- Amérique centrale -- Histoire -- 17e siècle.; Pirates -- Caraïbes (Région) -- Histoire -- 17e siècle.; Amérique centrale -- Histoire -- 17e siècle.; Espagne -- Colonies -- Amérique -- Histoire -- 17e siècle.; Indians; Buccaneers; Indians of Central America; Indians, Treatment of; Pirates; Spanish colonies; America; Caribbean Area; Central America; 1600-1699; History